2008
DOI: 10.1889/1.3069395
|View full text |Cite
|
Sign up to set email alerts
|

P‐46: Optimization of Subpixel Color Tiles for Mobile Displays

Abstract: A key issue for the optimization of subpixel color tiles for mobile displays is to maximize the image quality, often defined in terms of brightness or reflectance, and color saturation, while minimizing display power consumption. for the mirasol™ display based on MEMS technology, the RGBY quad is found to be a structure that achieves a balance between reflectance and color saturation. Simulation results based upon demonstration devices are presented with discussions about proper image quality metrics for mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…RGBY designs have been made and reported. 106 The color gamut of a simulated RGBY array is~27% of the sRGB specifications and provides an increase in contrast of 16% over RGB. Other physical factors in the device construction of the MEMS array combine with the color architecture to result in an overall reflectance of~23% (demonstrated at Display Week 2010).…”
Section: Mems (Electromechanical Interference Modulation)mentioning
confidence: 99%
“…RGBY designs have been made and reported. 106 The color gamut of a simulated RGBY array is~27% of the sRGB specifications and provides an increase in contrast of 16% over RGB. Other physical factors in the device construction of the MEMS array combine with the color architecture to result in an overall reflectance of~23% (demonstrated at Display Week 2010).…”
Section: Mems (Electromechanical Interference Modulation)mentioning
confidence: 99%
“…On the other hand, sub-pixel structure and SPR with quad-color tiles are still struggling to gain manufacturers' acceptance in mobile displays. 14 It is convinced that the conversion of tri-vectored color values to quad-vectors creates a degree of freedom so that we could optimize image quality by creating a new RMA.…”
Section: Introductionmentioning
confidence: 99%
“…It fulfills the most essential requirement of short switching time and good viewing angle [1]. However, this bend mode is not stable under zero voltage bias, because the elastic energy of splay is always less than the bend configuration M. Xu et al [2] and F. S. Yeung et al [3]- [4] suggested some kinds of stabilized bend mode named "No-Bias Bend" mode using high pretilt angles. However, further research effect is required for uniform high pretilt angles over large area.…”
Section: Introductionmentioning
confidence: 99%